Development and initial validation of the perceived instrumental effects of violence in sport scale - Parent, Sylvie; Radziszewski, Stephanie; Gillard, Allyson; Bélanger-Gravel, Ariane; Gagné, Marie-Hélène; St-Pierre, Elisabeth; Vertommen, Tine; Woodburn, Andrea (Frontiers in Sports and Active Living, 2024)
A growing body of research is looking into risk factors for interpersonal violence (IV) in sport. This research suggests the existence of several important risk factors, especially organizaIonal and social factors. One of these factors is the beliefs regarding instrumental effects of violence, defined by Roberts et al. (2020) as the belief that violence "is funcIonal for moIvaIng athletes and making them perform beher" (p. 11). Coaches may want to drive performance, deter failure, test resilience and commitment, develop toughness, assure interpersonal control, and promote internal compeIIon. In sum, available evidence suggests the risk of IV increases when coaches believe in the effecIveness of strategies involving IV to enhance athlete performance or perceive external approval for these pracIces. The studies presented in this arIcle seeks to develop and validate the Perceived Instrumental Effects of Violence in Sport (PIEVS) Scale in order to measure those beliefs in coaches. In study 1, item generaIon, expert consultaIon, cogniIve interviews, pilot test and item reducIon phases led to 25 items for the PIEVS around six dimensions. In study 2, exploratory factor analysis (EFA) was conducted with 690 coaches in order to determine the PIEVS factorial structure and the convergent and divergent validity of the scale was tested (long and short form). Our results suggested a one-factor soluIon for the PIEVS (25 items). This one-factor model provided an excellent fit to the data and a very good internal consistency. The PIEVS and empowering moIvaIonal climate were negaIvely correlated, which supported divergent validity as expected. The PIEVS was posiIvely correlated with the disempowering moIvaIonal climate and with sport ethic norms, which supported convergent validity as expected. These findings provide preliminary evidence for the appropriateness of the PIEVS Scale to measure perceived instrumental effects of violence in coaches.